Feasibility study of high-power electron linac for clinical X-ray ROAD-FLASH therapy system - Kutsaev, Sergey V.; Agustsson, Ronald; Boucher, Salime; Carriere, Paul; Ghoniem, Nasr; Kaneta, Kenichi; Kravchenko, Maksim; Li, Alan; Moro, Adam; Patel, Sohun; Sheng, Ke (Frontiers in Medical Engineering, 2024)
Introduction: This study examines how a practical source of X-ray radiation, capable of delivering unprecedented X-ray of 100 Gy/s at 1 m for X-ray FLASH radiotherapy can be designed. Methods: We proposed the design of a linac, capable of accelerating 18 MeV 8 mA electron beam with further conversion to bremsstrahlung X-rays. The design is based on L-band traveling wave accelerating structures with high power efficiency, operating in a short-burst/long-pulse regime that allows operating power supply in a regime, beyond its specifications. Results: This study demonstrates the feasibility of a high-power linac for a clinical X-ray FLASH therapy system, using detailed analysis and simulations. Despite ∼500x higher output than a standard clinical linac, the design utilizes available accelerator components for maximal practicality. Discussion: Recent studies have demonstrated that the FLASH effect that allows to effectively kill tumor cells while sparing normal tissue occurs when large dose rates (≥40 Gy/s) are delivered in less than 1 s. Photons are very attractive since modest energies of several MeV are needed, which can be achieved with compact and cost-efficient accelerators. However, since the efficiency of electron-to-photon conversion is only a few percent, the required beam intensity must be an order of magnitude higher than that state-of-the-art accelerators can provide. The proposed ROAD-FLASH accelerator layout allows achieving both the FLASH dose rate and superior dose conformity, comparing to the similar projects. The current paper focuses on providing a technical roadmap for building an economical and practical linear accelerator for ROAD X-ray FLASH delivery.